2020
DOI: 10.1016/j.jval.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Feasibility and Psychometric Properties of the ICEpop CAPability Measure for Adults and Its Use So Far in Economic Evaluation

Abstract: Objectives: Development of the ICEpop CAPability measure for Adults (ICECAP-A) was reported in 2012; use of certain capability measures was suggested in the context of social or long-term care soon afterward by decision-making organizations in the United Kingdom and The Netherlands. Despite enthusiasm for the ICECAP-A, this study represents the first attempt to collate evidence on its psychometric properties and its use in economic analysis.Methods: A systematic review of studies published between January 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Beside the original English language version, it is also available in German (32), Chinese (36), Welsh, Dutch, Danish, Persian and Italian languages (37). The ICECAP-A has a preference-based value set derived from the UK general population (30) and it is increasingly used in economic evaluations (38).…”
Section: Instrumentsmentioning
confidence: 99%
“…Beside the original English language version, it is also available in German (32), Chinese (36), Welsh, Dutch, Danish, Persian and Italian languages (37). The ICECAP-A has a preference-based value set derived from the UK general population (30) and it is increasingly used in economic evaluations (38).…”
Section: Instrumentsmentioning
confidence: 99%
“…Previous factor analysis comparing the ICECAP-A with the items of EQ-5D-5L (31) and EQ-5D-3L (13,15) found that these instruments measure two different constructs and therefore provide potentially different information. A recent systematic literature review found inconsistencies between the ICECAP-A and EQ-5D instruments, suggesting that the ICECAP-A is most appropriately regarded as a complement for and not a substitute to the EQ-5D-3L and EQ-5D-5L in particular (32). The ICECAP-A has a preference-based value set derived from the UK general population (24) and it is increasingly used in economic evaluations (32).…”
Section: Instrumentsmentioning
confidence: 99%
“…A recent systematic literature review found inconsistencies between the ICECAP-A and EQ-5D instruments, suggesting that the ICECAP-A is most appropriately regarded as a complement for and not a substitute to the EQ-5D-3L and EQ-5D-5L in particular (32). The ICECAP-A has a preference-based value set derived from the UK general population (24) and it is increasingly used in economic evaluations (32). The simple addition of ICECAP-A level sum scores ranges from 5 to 20, with higher scores representing better capabilities.…”
Section: Instrumentsmentioning
confidence: 99%
“…For all indices, a value of < 0.2 was considered small, 0.2-0.5 moderate and > 0.5 large responsiveness [23]. The range of the un-weighted score was 16 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and for the tariff score was 1 (0-1) with higher scores on both representing higher capability. Age differences in responsiveness were investigated by subgroup analysis using a group < 65 years of age and a group ≥ 65 years of age.…”
Section: Responsivenessmentioning
confidence: 99%
“…A systematic review by Afentou and Kinghorn [9] and a comparative review by Helter et al [10] found evidence available on reliability, content validity, construct validity and responsiveness of the ICECAP-A measure in various populations, but so far, most evidence relates to the original UK version [9,10]. In the Danish context, only one reliability study of the ICECAP-A in the general population exists [11].…”
Section: Introductionmentioning
confidence: 99%